The Risk for Obstructive Sleep Apnea and Cognitive Function of High School Student - Ferrany Thifla Aghni Brilliana; Nurfitri - Bustamam; Cut - Fauziah (Saintika Medika, 2020)
Obstructive sleep apnea (OSA) is a common sleep disorder characterized by recurrent partial and/or total upper airway obstruction during sleep resulting in hypoxemia and arousal. One of the risk factors for OSA is obesity which its prevalence increased in Indonesia. OSA has a negative effect on cognitive function broadly. This study was aimed to determine the association between risk for OSA and cognitive function in high school students with obesity at Sulthon Aulia Boarding School, Bekasi. The study used a cross-sectional design and a simple random sampling technique. Data were taken using the Berlin Questionnaire and the Montreal Cognitive Assessment Indonesia version (MoCA-Ina) Questionnaire. The sample size is 47 subjects with inclusion criteria had overweight or obese body mass index (BMI) and were willing to be the research subjects. Subjects with a history of head injury, smoking, drinking alcohol, and taking sedative drugs were excluded from the study.  There were differences in BMI and neck circumference between high-risk subjects for OSA and low-risk subjects for OSA. The risk level for OSA was significantly associated with cognitive function (p = 0.001; OR =12.727).  High-risk subjects for OSA are recommended to lose weight and perform a polysomnographic evaluation.